Development of a WirelessHART - EnOcean Adapter for Industrial Applications - Renaux, Douglas Paulo Bertrand; Arcari, Felipe D'Agostini; Costa, Celso; Pereira, Carlos Eduardo; Netto, João Cesar; Torres, Guilherme; Souza, Matheus; Müller, Ivan (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2017)
Wireless Sensor Networks present several advantages when compared to wired ones, among them, the low consumption and simplicity of installation. In some cases, energy consumption may be so low as to allow the use of energy harvesting techniques, as in the case of EnOcean protocol. In other networks, it is necessary to meet specific requirements, such as in industrial ones, where communication must be robust, deterministic and safe. This is achieved by WirelessHART protocol. Both types of networks have limitations, such as EnOcean's inability to determinism and low dynamics of joining and maintenance of WirelessHART. This work presents a proposal to minimize these limitations, through the union of these networks, by the development of an WirelessHART - EnOcean adapter. The adapter adds the functionality of intermittent and battery-free sensors to a WirelessHART network in order to provide the use of EnOcean devices in industrial environments. Aiming the validation of the adapter, a case study is proposed where the functionality of both networks is verified. For the development of the proposal, hardware and firmware changes are made to a WirelessHART device and the development of hardware adapter and an application to integrate both networks.